Distribution, contamination status and bioavailability of trace metals in surface sediments along the southwest coast of India. (March 2021) - Cyriac, M.; Gireeshkumar, T.R.; Furtado, C.M.; Fathin, K.P. Fahad; Shameem, K.; Shaik, Adnan; Vignesh, E.R.; Nair, M.; Kocherla, M.; Balachandran, K.K.
Abstract: This study investigates the influence of upwelling induced seasonal hypoxia in the sediment-water interface on the distribution, bioavailability and geochemical partitioning of selected trace metals in surficial sediments along the southwest coast of India based on two successive cruises. The first cruise was during the southwest monsoon (SWM) season when coastal waters exhibited intermittent bottom hypoxia due to upwelling. The second cruise during the northeast monsoon (NEM) season was characterised by a uniformly warm and well-oxygenated water column in the study region. The results showed that grain size, organic carbon and Fe are the major factors influencing the distribution of trace metals in the surface sediments. Based on the geochemical indices (contamination factor, enrichment factor and geo-accumulation factor), the study region appears to be moderately contaminated by Ni, Cr, and Pb. Based on the ecological risk assessment criteria, the enrichment of Pb, Cr and Ni may cause adverse effects on the benthic organisms. The fractionation studies demonstrated that the major pathway of metal deposition in the sediment is lithogenic. The data also showed that labile and organic fractions are the second dominant forms, while other fractions (exchangeable and carbonate) are insignificant. The consistency in the reactive Fe concentrations during SWM and NEM could be due to the absence of Fe dissolution in sediments under mild reducing condition (intermittent hypoxia). In addition to the above, an enrichment of organic matter also leads to increased deposition of trace metals in sediments. Conversely, the secondary phase enrichment factor and risk assessment code calculated based on the metal fractionation data indicated low risk and contamination along the southwest coast of India except for Zn that showed moderate contamination in some transects. The study provides the need for regular geochemical assessment to control metal pollution in the coastal environment, which is a major resource of the fishery. Highlights: Seasonal distribution, and bioavailability of trace metals in sediments along the southwest coast of India were examined. The study region appears to be moderately contaminated by Ni, Cr, and Pb. The enrichment Pb, Cr and Ni may cause adverse effects on the benthic organisms. The major pathway of metal deposition in the sediment is lithogenic. Among non-residual trace metals, Fe/Mn hydroxide and organic matter bound forms are dominant.